Α-granule biogenesis: from disease to discovery. (17th February 2017) - Chen, Chang Hua; Lo, Richard W.; Urban, Denisa; Pluthero, Fred G.; Kahr, Walter H. A.
Abstract: Platelets are critical to hemostasis and thrombosis. Upon detecting injury, platelets show a range of responses including the release of protein cargo from α-granules. This cargo is synthesized by platelet precursor megakaryocytes or endocytosed by megakaryocytes and/or platelets. Insights into α-granule biogenesis have come from studies of hereditary conditions where these granules are immature, deficient or absent. Studies of Arthrogryposis, Renal dysfunction, and Cholestasis (ARC) syndrome identified the first proteins essential to α-granule biogenesis: VPS33B and VPS16B. VPS33B and VPS16B form a complex, and in the absence of either, platelets lack α-granules and the granule-specific membrane protein P-selectin. Gray Platelet Syndrome (GPS) platelets also lack conventionally recognizable α-granules, although P-selectin containing structures are present. GPS arises from mutations affecting NBEAL2. The GPS phenotype is more benign than ARC syndrome, but it can cause life-threatening bleeding, progressive thrombocytopenia, and myelofibrosis. We review the essential roles of VPS33B, VPS16B, and NBEAL2 in α-granule development. We also examine the existing data on their mechanisms of action, where many details remain poorly understood. VPS33B and VPS16B are ubiquitously expressed and ARC syndrome is a multisystem disorder that causes lethality early in life. Thus, VPS33B and VPS16B are clearly involved in other processes besides α-granule biogenesis. Studies of their involvement in vesicular trafficking and protein interactions are reviewed to gain insights into their roles in α-granule formation. NBEAL2 mutations primarily affect megakaryocytes and platelets, and while little is known about NBEAL2 function some insights can be gained from studies of related proteins, such as LYST.